Haemodynamic effects of sodium nitroprusside in 21 subjects with congestive heart failure. Issue 2 (February 1979) - Lukes, S A; Romero, C A; Resnekov, L
Abstract : Twenty-one patients in severe congestive heart failure refractory to conventional medical management were treated with sodium nitroprusside on 22 occasions. On 14 occasions (responders) there was significant improvement in clinical and haemodynamic indices. On 8 occasions (non-responders) hypotension developed without haemodynamic improvement and nitroprusside treatment had to be abandoned. The initial mean arterial pressure and the capillary wedge pressure tended to be higher in the responders while the cardiac index tended to be higher in the non-responders. The systemic vascular resistance was higher in the responders than in the non-responders (2560 +/- 160 vs 1800 +/- 180 dynes s cm-5, P less than 0.001). All of the responders had systemic vascular resistance greater than 1900 dynes s cm-5, while only one of the non-responders had a systemic vascular resistance in this range. Thus, a variable response to vasodilator therapy for congestive cardiac failure is documented. The favourable response appears to be limited to patients with a high systemic vascular resistance.